Do you See what I See? Signaling Effects of Gender and Firm Characteristics on Financing Entrepreneurial Ventures - Eddleston, Kimberly A.; Ladge, Jamie J.; Mitteness, Cheryl; Balachandra, Lakshmi (Entrepreneurship Theory and Practice, 2016)
In this study, we examine whether female entrepreneurs are held to a different standard than male entrepreneurs in obtaining financing from banks. To test this idea, we draw from the literature on signaling theory to propose that characteristics specific to the firm and the entrepreneur act as a means to communicate (i.e., signal) the inherent quality of the venture and thus impact the amount of capital the entrepreneur is able to obtain. We then explore the moderating role of gender based on gender role congruity theory to argue that capital providers reward the business characteristics of male and female entrepreneurs differently to the disadvantage of women.